Professional Development Model for ESP Teachers Working at Engineering Universities - K. M. Inozemtseva; N. O. Troufanova; A. K. Krupchenko (Высшее образование в России)
The article describes application of pedagogical modelling in designing professional development (PD) syllabus for Language for Specific Purposes (LSP) teachers working at Russian engineering universities. The authors consider meaningful factors defining professional requirements for LSP tertiary teachers and view the problems of LSP teachers’ professional development from engineering pedagogy perspective. They substantiate the necessity of developing the Profile of LSP tertiary teachers’ professional competencies as a standard description of qualification requirements for this specialty. The authors analyze the results of LSP teachers’ diagnostics that revealed methodo-logical deficit of the respondents in theory and practice of cross-disciplinary approach to teaching Language for Specific (Engineering) Purposes. The organizational and pedagogical model based on qualification requirements of the above Profile is proposed as the basis of professional development syllabus design, selection of teaching methods and assessment of learning outcomes. The addressees of the above model are tertiary LSP teachers willing to improve their professional competences and cross-disciplinary integrative skills in order to develop foreign language professional communicative competence of engineering students.